You have new items in your feed. Click to view.
Q: Solve for x. 2x = -7 + 3x - 6
A: 2x = -7 + 3x - 6 2x = 3x - 13 2x - 3x = -13 -x = -13 x = 13
Question
Updated 2/18/2017 2:59:26 AM
Edited by Andrew. [2/18/2017 2:58:35 AM]
Rating
3
2x = -7 + 3x - 6
2x = 3x - 13
2x - 3x = -13
-x = -13
x = 13

Questions asked by the same visitor
work this plz 2x = -7 + 3x- 6 find x
Question
Updated 124 days ago|2/17/2018 12:29:51 PM
2x = -7 + 3x - 6
2x = 3x - 6 - 7
2x = 13 - 3x
-x = -13
x = -13/-1
x = 13
Added 124 days ago|2/17/2018 12:29:51 PM
*
Get answers from Weegy and a team of really smart lives experts.
S
L
Points 253 [Total 271] Ratings 0 Comments 183 Invitations 7 Online
S
L
Points 130 [Total 130] Ratings 0 Comments 130 Invitations 0 Offline
S
L
R
Points 125 [Total 276] Ratings 1 Comments 5 Invitations 11 Offline
S
R
L
R
P
R
P
R
Points 66 [Total 734] Ratings 0 Comments 6 Invitations 6 Offline
S
1
L
L
P
R
P
L
P
P
R
P
R
P
R
P
P
Points 62 [Total 13329] Ratings 0 Comments 62 Invitations 0 Offline
S
L
1
R
Points 34 [Total 1450] Ratings 2 Comments 14 Invitations 0 Offline
S
L
Points 10 [Total 187] Ratings 0 Comments 0 Invitations 1 Offline
S
Points 10 [Total 13] Ratings 0 Comments 10 Invitations 0 Offline
S
Points 10 [Total 10] Ratings 0 Comments 0 Invitations 1 Offline
S
Points 2 [Total 2] Ratings 0 Comments 2 Invitations 0 Offline
* Excludes moderators and previous
winners (Include)
Home | Contact | Blog | About | Terms | Privacy | © Purple Inc.